Małopolskie dzienniki regionalne w procesie tabloidyzacji przekazu na temat wyborów samorządowych – płaszczyzna formy - Hess, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The tabloidization of political journalism is inseparable from the developing process of the mediatization of politics, which is based on political entities adjusting their activities to the logic of the media, and the consequent changes this causes in media coverage. The purpose of this paper is to answer the question of whether the coverage of the local government election campaign by the regional dailies of Małopolska showed features typical of tabloids. The author presents the results of an analysis of the Kraków dailies (Dziennik Polski, Gazeta Krakowska and the local insert to Gazeta Wyborcza), in terms of five criteria of discourse differentiation: entertainization/infotainment, the rhetoric of dispute, personalization, markedness, and simplification. The analysis covered two aspects of the discourse: its form and content. This paper presents the results of an analysis of the tabloidization of media coverage in relation to its form and compares the results of surveys in 2006 and 2010.